2020
DOI: 10.1016/j.jvs.2019.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with elimination of type II endoleak during the first year after endovascular aneurysm repair

Abstract: Objective: The natural history of endoleak type II (ET II) after endovascular aneurysm repair (EVAR) is still debatable. The aim of this study was to examine the presence of preoperative and postoperative factors associated with persistence of ET II during the initial 12-month follow-up period.Methods: A two-center retrospective study including patients subjected to EVAR from 2006 to 2017 was undertaken. Patients with ET II at 1-month computed tomography angiography (CTA) were categorized into two groups, reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In addition, it was concluded that the presence of hostile neck anatomy, infrarenal neck angulation, neck length, and patency of the IMA are not predictive of AAA sac remodeling after EVAR. Surprisingly, the patency of the IMA is not related to AAA sac remodeling even though the IMA is a common origin of persistent type II endoleaks, which has repeatedly been shown to correlate to AAA sac remodeling 7,26,35,36 .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it was concluded that the presence of hostile neck anatomy, infrarenal neck angulation, neck length, and patency of the IMA are not predictive of AAA sac remodeling after EVAR. Surprisingly, the patency of the IMA is not related to AAA sac remodeling even though the IMA is a common origin of persistent type II endoleaks, which has repeatedly been shown to correlate to AAA sac remodeling 7,26,35,36 .…”
Section: Discussionmentioning
confidence: 98%
“…However, previous studies showed that EL 2 occurrence, sac expansion, and need for reintervention are all affected by anatomic and hemodynamic factors [ 14 , 22 ]. Patients with multiple contributing vessels related to EL 2 and inflow–outflow patterns, as well as the presence and distribution of endoluminal thrombus before repair, may lead to persistent EL 2 and subsequently, multiple reinterventions, and even open conversions, to achieve sac exclusion [ 1 , 4 , 23 , 24 ]. In addition, hemodynamic alterations after a successful embolization may lead to the evolution of new endoleaks, including type 2.…”
Section: Discussionmentioning
confidence: 99%
“…Early and accurate diagnosis is very important for the treatment and prognosis of aortic constriction. At present, the clinical diagnosis of aortic constriction often uses chest X-ray, computed tomography (CT), magnetic resonance imaging (MRI), ultrasound, contrast, and other imaging methods [8]. Among them, chest radiographs are cheap and suitable for preliminary screening of aortic constriction, but their diagnostic sensitivity is too low.…”
Section: Introductionmentioning
confidence: 99%